2015
DOI: 10.2217/epi.15.22
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A Moderates Cognitive Decline in Subjects with Mild Cognitive Impairment: Replicated Evidence from Two Mild Cognitive Impairment Cohorts

Abstract: Epigenetic dysregulation has been associated with cognitive decline and Alzheimer's disease. The present study investigated associations between common SNPs in genes regulating DNA methylation and age-related changes in cognitive decline in two independent prospective cohorts of patients suffering from mild cognitive impairment. An association between the rs1187120 SNP in DNMT3A and annual decline in cognitive functioning was discovered and replicated, suggesting that DNMT3A moderates cognitive decline in subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…It was described elsewhere that DNMT3a and DNMT3b are essential for memory formation and that they participated in neuronal and synaptic plasticity changes. Recently, it is has been reported that DNMT3b moderates cognitive decline in subjects with mild cognitive impairment [ 41 , 42 ]. The significant changes found in Dnmt1 and Dnmt3b in young 5XFAD lead to higher cytosine methylation, prior to the development of AD hallmark in this mouse, underlying the earlier participation for methylation processed at the onset of the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…It was described elsewhere that DNMT3a and DNMT3b are essential for memory formation and that they participated in neuronal and synaptic plasticity changes. Recently, it is has been reported that DNMT3b moderates cognitive decline in subjects with mild cognitive impairment [ 41 , 42 ]. The significant changes found in Dnmt1 and Dnmt3b in young 5XFAD lead to higher cytosine methylation, prior to the development of AD hallmark in this mouse, underlying the earlier participation for methylation processed at the onset of the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in binding, however, did not correlate with enhanced promoter methylation ( Baets and others 2015 ). Recently, a genetic study on single-nucleotide polymorphisms (SNPs) in DNMT3A revealed an association with a particular genotype in an SNP and greater cognitive decline in patients with mild cognitive impairment ( Chouliaras and others 2015 ) ( Box 1 ).…”
Section: Dnmts In Neurodegeneration and Neuropsychiatric Disordersmentioning
confidence: 99%
“…DNA methylation of CpG units by DNA methyltransferases (DNMTs) disrupts the binding of transcription factors and attracts methyl-CpG-binding domain proteins that are associated with gene silencing and chromatin compaction [ 111 ]. An association was discovered between the rs1187120 SNP in DNMT3A and annual decline in cognitive functioning, suggesting that DNMT3A moderates cognitive decline in subjects with mild cognitive impairment [ 112 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%